1984
DOI: 10.1051/rphysap:01984001909080700
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and pressure induced phase transition in IV-VI compounds

Abstract: The crystal structure of SnS has been investigated as a function of temperature by elastic neutron scattering from 293 K to 1 000 K. SnS undergoes a second order displacive phase transition from the α-phase (B16, Pbnm) to the high temperature β-phase (B33, Cmcm) at 887 K. The mean square displacement of the Sn atom which is isotropic at room temperature becomes increasingly anisotropic and anharmonic near Tc. Energy dispersive X-ray diffraction experiments have been performed on IV-VI semiconductors PbS, PbSe,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
82
6

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(98 citation statements)
references
References 17 publications
10
82
6
Order By: Relevance
“…The diffraction patterns obtained at higher than 45.4 GPa can been indexed to the B2 phase, and this is consistent with previous reports. 6,7,12 Two experimental factors influenced the precise structural determination in our previous two experimental runs. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The diffraction patterns obtained at higher than 45.4 GPa can been indexed to the B2 phase, and this is consistent with previous reports. 6,7,12 Two experimental factors influenced the precise structural determination in our previous two experimental runs. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Using resistance measurements, Samara et al found that PbS has a phase transition at 2.3-2.5 GPa. 4 X-ray diffraction (XRD) studies have shown that the B1 phase transforms into an intermediate phase at 2-3 GPa, [5][6][7][8][9][10][11][12] and into a CsCl-type structure (B2) at higher than 21.5 GPa. 6,7 However, the detailed structure of the intermediate phase is controversial.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…First structural studies under high pressure were performed using X-ray film methods [8]. Later, the compression behaviour of PbS was studied by means of highpressure energy dispersive X-ray powder diffraction (HP-EDX) up to 35 GPa [9,10,11,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The phase transition at 2.2 GPa [7] to a β-phase having orthorhombic symmetry was characterised as a first order transition [8,10,11]. However, the structure of this phase is still a matter of debate.…”
Section: Introductionmentioning
confidence: 99%